Insight into the Dyeability of Bio-Based Polyamide 56 by Natural Dyes - Chenchen Sun; Jiaqing Wu; Ying Wang (Chemistry, 2025)
Bio-based polyamide 56 (PA56) is a new sustainable material in the polyamide family. In this study, dyes suitable for PA56 fibers were experimentally screened from natural plants rich in pigments. The results showed that the preferred natural dyes for PA56 fabric are turmeric for a yellow hue, madder for a red hue, catechu for a brown hue, and indigo for a blue hue. A green hue was achieved by the two-bath dyeing method using indigo and turmeric, respectively. For a dyability comparison with conventional PA6 and PA66, PA56, PA6, and PA66 fabrics were woven under identical conditions and dyed with turmeric, madder, catechu, and commercial indigo extracts. PA56 fabric exhibited the best dye uptake and the fastest dyeing rate (PA56 > PA6 > PA66). The reason for the excellent dyeability of PA56 fibers was analyzed in terms of differential scanning calorimetry measurement and molecular dynamics simulations. The results showed that the lowest crystallinity was exhibited by PA56 (PA56 < PA6 < PA66); in addition, PA56 displayed the largest fractional free volume (PA56 > PA6 > PA66). These structural characteristics contribute to the excellent dyeability of PA56 fibers. Therefore, PA56 fibers are promising materials, as they are derived from a sustainable source and have superior dyeing properties compared to PA6 and PA66 fibers.